Pengaruh penambahan bubur rumput laut merah (Eucheuma spinosum) terhadap mutu karakteristik masker peel off - Dahlia Dahlia; Desmelati Desmelati; Maya Puspita (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
The aims of this study was to analyze the effect of adding red seaweed (Eucheuma spinosum) porridge to the quality characteristics of gel peel off masks. The main materials used in this study were E. Spinosum and other basic subtances of peel off mask. Research was an experimental study that using a non-factorial completely randomized design method with four levels of treatments, namely with F0 treatment (without adding the seaweed porridge), F1 (by adding 10 % of seaweed porridge), F2 (by adding 15 % of seaweed porridge), F3 (by adding 20 % of seaweed porridge). From the research results, it was found that the addition of red seaweed (Eucheuma spinosum) porridge had a significant effect on the characteristics, organoleptic quality and antioxidant content of peel off masks. F3was the best treatment which had an antioxidant content of 66 ppm. In the organoleptic assessment, the peel off mask with F3 treatment was preferred because it had a distinctive appearance and aroma from red seaweed (Eucheuma spinosum).